Men and memories : autobiographical recollections and reflections - Jayewardene, Junius Richard (New Delhi : Vikas Pub. House, 1992)
Reminiscences of a former president of Sri Lanka; covers the period, 1950-1980.
Keywords: Jayewardene, Junius Richard; Presidents -- Sri Lanka -- Biography; Sri Lanka -- Politics and government